Assortative breeding experiment in a songbird suggests telomere length is determined during early life rather than at conception - Xiong, Ye ; 0000-0002-7903-9375; Melgar, Julian; Tobler, Michael; Hasselquist, Dennis (Scientific Reports, 2025)
Telomere length (TL) early in life often shows high heritability and may predict telomere shortening later in life and life expectancy. Yet, there is limited data about what influences TL and TL change at early developmental stages. It is debated whether early-life TL is determined at conception or shaped by early environmental conditions. Here, we investigate whether TL and telomere shortening are set close to conception. We assortatively paired zebra finches (Taeniopygia guttata) based on their TL when nestlings, forming two parental pair groups with either ‘short’ or ‘long’ TL. We then measured TL in the offspring of these pairs at the embryo and nestling stages. In embryos, TL did not differ between offspring from the two parental pair groups. However, in nestlings, particularly in sons, offspring TL matched parental TL. Our results suggest that early-life TL itself is not determined at conception. Instead, telomere shortening rate before and just after hatching appears to determine early postnatal TL. These findings highlight that early development is critical for telomere shortening during early life stages and that it may be a key process underlying the similarity in early-life TL between parents and offspring, potentially affecting telomere dynamics throughout life.
Keywords: Ageing; Early development; Fetal programming; Sex differences; Zebra finch